Citizen science records describe the distribution and migratory behaviour of a piscivorous predator, Pomatomus saltatrix. (16th May 2018) - Brodie, S; Litherland, L; Stewart, J; Schilling, H T; Pepperell, J G; Suthers, I M
Abstract: Understanding the processes driving species distributions is a key question in ecology, yet obtaining pertinent data for many species can be challenging. Tag-recapture data from voluntary recreational fisheries programmes is an undervalued citizen science data resource and can provide valuable observation records for data-poor species. Here, we highlight the utility of such data by compiling four tag-recapture datasets ( n = 20 878 tags) to describe the movements and distribution of a piscivorous predator, tailor Pomatomus saltatrix, with respect to their environment. We compared species distribution models that explored a trade-off between temporal duration and spatial extent. Both models revealed sea surface temperature (SST) was an important factor in describing the distribution and density of tailor. However, the model with broader spatial extent indicated a non-linear response to SST, peaking at 21.5°C, while the model with temporal longevity showed a linear SST response. This disjunct showcases the importance of building models across an adequate geographic extent to ensure covariate responses are not truncated. This is the first study to comprehensively describe the distribution and migrations of adult tailor across their eastern Australian distribution. The results are discussed in light of ocean warming along eastern Australia, and the subsequent implications for using tag-recapture data in fisheries management.